Synergistic antibacterial effect of apigenin with Î²-lactam antibiotics and modulation of bacterial resistance by a possible membrane effect against methicillin resistant Staphylococcus aureus - Akilandeswari, K.; Ruckmani, K. (Cellular and Molecular Biology, 2016)
Methicillin-resistant Staphylococcus aureus (MRSA) infections are easily spread among infected patients, where resistance has dramatically increased resulted in serious health issues. Therefore, there is a need to develop alternative natural or combination drug therapies. Apigenin (AP) is a natural poly phenolic flavonoid has been found to possess many beneficial biological actions. The aim of this study was to investigate the anti-MRSA efficacy and synergistic effect of apigenin (AP) and in combination with ampicillin (AM) and ceftriaxone (CEF). The antibacterial activity of apigenin was assessed by the broth macro dilution, checkerboard micro dilution method and time-kill assay.  The mode of action was studied by outer and inner membrane permeabilisation assays, scanning electron microscopy and transmission electron microscopy. The minimum inhibitory concentration (MIC) of apigenin against gram positive and gram negative strain ranged from 32.5 to 62.5µg/ml. In checkerboard method apigenin markedly reduced the MIC of the antibiotics ampicillin 800 µg/ml shifted to 107 µg/ml (AM+AP) and ceftriaxone 58 µg/ml shifted to 2.6 µg/ml (CEF+AP) against MRSA. The synergistic activity of ampicillin and ceftriaxone plus apigenin combinations with FIC indices (CI) between 0.18-0.47. The modulation of methicillin-resistance by apigenin significantly enhanced the activities of ampicillin and ceftriaxone. The result of time-kill assays of the two drug combinations AM +AP and CEF+AP against MRSA showed significant inhibitory effect and reduced the colony count by approximately 99% after 8 h The results for outer membrane (OM) and inner membrane (IM) permeabilization showed that ampicillin and ceftriaxone in combination with apigenin damaged MRSA cytoplasmic membrane and caused subsequent leakage of intracellular constituents. Electron microscopy clearly showed that the above said combination also caused marked morphological damage of cell wall, cell shape and plasma membrane of this strain. From these results, it can be concluded that apigenin has the synergistic effect with ampicillin and ceftriaxone to reverse bacterial resistance against MRSA.